Manajemen Peningkatan Mutu Berbasis Sekolah Dalam Meningkatkan Peran Serta Warga Sekolah dan Masyarakat - Iswanto, Juni (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2015)
Implementation of education reform requires the readiness of all parties to change in order to improve the performance of the national education system, one of which is the school-based quality improvement management (MPMBS). As a consequence of regional autonomy, MPMBS is defined as management that provides greater autonomy, provides flexibility to schools and encourages direct participation of school and community members to improve school quality. MPMBS is part of the school-based management (SBM) which will eventually become MBS. The objectives of MPMBS are (1) to help schools explain current and future management, (2) encourage and support community participation, (3) encourage school-making decision making. The success of school-based quality improvement management is determined by a strong managerial presence, so that the principal can create a conducive and enjoyable working environment. Teachers should also be creative in improving classroom management, since teachers are role models and direct models of students in the classroom. While community empowerment, in MPMBS, is intended to optimize effectively and efficiently on the performance of school elements, namely principals, teachers, administrative staff, pupils, parents and community.